PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BAGI SISWA KELAS I MI MIFTAHUL INAYAH SLARANG LOR TEGAL - Sugiono Putra, Hafizh Akbar; Budi Nurmana.M.S., Ayyub Hamdanu; Sulartopo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2026)
The low reading ability of early grade students in Islamic Elementary Schools (Madrasah Ibtidaiyah) remains a problem in Indonesian language learning, particularly in recognizing letters, combining syllables, and reading simple sentences. This problem is influenced by the use of conventional and less interactive learning media. This study aims to design interactive Indonesian language learning media using the Multimedia Development Life Cycle (MDLC) model and analyze the results of its application on the reading ability of first grade students at MI Miftahul Inayah Slarang Lor, Tegal. The method used is development research with MDLC stages including concept, design, material collection, assembly, testing, and distribution. Data collection techniques were carried out through observation, interviews, literature studies, and product trials with teachers and students. The results showed that the developed interactive learning media was declared suitable for use based on functional tests (black box testing) and user responses. In addition, there was an increase in students' reading ability based on a comparison of pre-test and post-test results after the media was used. The conclusion of this study shows that interactive multimedia-based learning media is effective in improving the reading ability of early grade students and can be used as an alternative medium for Indonesian language learning in Islamic Elementary Schools.